How to Write Lyrics: Better Words for Your Songs - Rooksby, Rikky (Globe Trade, 2021)
Lyrics sheds light on all aspects of writing lyrics for music and will make lyricists and songwriters feel more confident and creative when they tackle lyrics. It's perfect for all songwriters: those who don’t like their own lyrics and find lyrics difficult to write, experienced writers looking for a creative edge, and those offering lyrics to set to music in a partnership. The book discusses channeling personal experiences into lyrics, overcoming writer's block, the right lyrics for a bridge, the separation between lyrics and poetry, exploring imagery and metaphor, avoiding clichés, and more. It also offers tips on the various styles of lyrics, from protests, spirituals, and confessionals to narratives and comic songs. New to this edition are artist and song references throughout to reflect musical history to date. Also, a new section provides examples of taking lyric ideas right through the drafting process, illustrating development and re-drafting and using a handful of contrasting approaches.